Role of Tear Film Inflammatory Biomarkers in the Diagnosis and Severity Grading of Allergic Conjunctivitis - Shafqat Ali Shah, Muhammad Bilal, Muhammad Tariq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Allergic conjunctivitis is an IgE-mediated ocular surface disease characterized by mast-cell activation and Th2-driven inflammation resulting in itching, redness, and chemosis. Current clinical grading systems are subjective and may fail to identify subclinical inflammation. Tear film inflammatory biomarkers offer a promising objective tool for improving diagnostic accuracy and severity stratification. Objectives: To evaluate tear film inflammatory biomarkers in patients with allergic conjunctivitis and determine their association with clinical severity grades. Methodology: The study was a cross-sectional study conducted at the Department of Ophthalmology unit BKMC Mardan from January 2022 to June 2022. 100 patients with clinically diagnosed allergic conjunctivitis and 40 healthy controls at a tertiary-care ophthalmology unit. Tear samples were collected using sterile microcapillary tubes and analyzed for interleukin-4, interleukin-5, interleukin-13, eutaxon, and matrix metalloproteinase-9 using enzyme-linked immunosorbent assay kits. Disease severity was graded using the Bonini classification. Data were analyzed in SPSS version 24.0. Independent t-tests compared biomarker levels between groups, while Pearson correlation and multivariate regression assessed associations with disease severity. Results: The mean age of patients was 31.8 ± 9.7 years, with 58% males. Tear concentrations of all measured biomarkers were significantly higher in allergic conjunctivitis patients compared with controls (p < 0.001). Mean IL-5 levels were 42.6 ± 10.4 pg/mL in cases versus 15.2 ± 5.1 pg./mL in controls (p < 0.001). Biomarker levels increased progressively across mild, moderate, and severe disease. Severe cases showed the highest mean MMP-9 levels (168.3 ± 35.6 ng/mL). IL-5 and eutaxon demonstrated strong positive correlations with disease severity (r = 0.71 and 0.68, respectively; p < 0.001). Conclusion: Tear film inflammatory biomarkers, particularly IL-5 and MMP-9, are significantly associated with disease severity and provide objective indicators for diagnosis and severity grading in allergic conjunctivitis. Keywords: Allergic conjunctivitis; Tear biomarkers.